ASSESSING ORGANIC LINKEDIN EFFECTIVENESS FOR BRAND IDENTITY AND LEAD GENERATION: A CASE STUDY CREATIVEUNOIA AS AN INDEPENDENT PRODUCTION HOUSE - Jihan Maghfira Nasery (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study evaluates whether a structured organic LinkedIn strategy can strengthen brand identity, improve professional visibility, and generate early lead indicators for Creativeunoia, an independent Indonesian production house. The research used a qualitative single case design supported by descriptive platform analytics. Primary data came from a semi structured interview with the founder and a focus group discussion with three other founding members. Secondary evidence included company records, industry literature, competitor observations, and LinkedIn analytics. Internal analysis applied the Resource Based View, Marketing Mix 7P, and STP, while external and integrated analysis used PESTLE, customer analysis, SWOT, and TOWS. The resulting strategy published three weekly content pillars for six weeks: brand identity, portfolio highlights, and thought leadership, combined with targeted professional outreach. The inactive page generated 3,651 impressions, 1,646 clicks, 65 reactions, 2 reposts, and reached 35 organic followers, approximately 62 percent of whom worked in creative and media related industries. Outreach to 30 professionals produced 18 responses, five high intent discussions, and one scheduled studio visit. The findings indicate that consistent, process oriented, identity driven content can convert internal creative capability into credible professional visibility and early business opportunities without paid advertising.